2020
DOI: 10.1186/s13104-019-4882-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of lost to follow-up among women under Option B+ PMTCT program in western Ethiopia: a retrospective follow-up study

Abstract: Objective: Although Ethiopia has been implementing Option B+ program, LTFU of women from the Option B+ program is one of the challenges that minimizes its implementation. Thus, this study assessed the incidence and predictors of LTFU among women under Option B+ PMTCT program in western Ethiopia. An institution-based retrospective follow-up study was conducted. A cox proportional hazards regression model was fitted to identify predictors of LTFU. A Hazard ratios with 95% confidence CI was computed and all predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 20 publications
(27 reference statements)
11
13
1
Order By: Relevance
“…The risk of LTFU among women who were on ART before PMTCT enrolment was lower than those who enrolled newly to PMTCT. This nding agreed with studies done in in different countries in African region (19,23,30). The possible explanations for this might be a known HIV woman and on ART before enrolment had experienced with ART treatment and might have good awareness about ART treatment, drug side effects and drug adherence than a newly enrolled woman.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The risk of LTFU among women who were on ART before PMTCT enrolment was lower than those who enrolled newly to PMTCT. This nding agreed with studies done in in different countries in African region (19,23,30). The possible explanations for this might be a known HIV woman and on ART before enrolment had experienced with ART treatment and might have good awareness about ART treatment, drug side effects and drug adherence than a newly enrolled woman.…”
Section: Discussionsupporting
confidence: 90%
“…The current study showed that risk of LTFU among women who are residing in rural area is higher as compared to women residing in urban. Supportive ndings were reported from previous studies in Ethiopia and Brazil (10,30,48). Possible explanations for this might be remote area mothers are forced to travel long distances in order to get the nearest hospital, which necessarily involves high costs which leads LTFU (16) and cannot easily get transport services due to poor /lack of road construction, makes women to walk long distances by bare foot, this leads them less likely to adhere to option B+ strategy (31) and resulting in missing the appointments (15,32).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The rate of loss-to-follow-up in most of the sub-Saharan countries range from as low as 9.6% to a high of 61% depending on the level of PMTCT cascade and settings [ 17 ]. The prevalence rate of LTFU is estimated to be between 9 and 14.8 per 1000 person-months of the option B+ cascade [ 18 ]. LTFU disrupt the Option B+ cascade and increase the risk of mother-to-child HIV transmission, and lead to poor health outcomes for both the mother and child including advancing of HIV stages and maternal and child mortality [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence rate of LTFU is estimated to be between 9 and 14.8 per 1000 person-months of the option B+ cascade [ 18 ]. LTFU disrupt the Option B+ cascade and increase the risk of mother-to-child HIV transmission, and lead to poor health outcomes for both the mother and child including advancing of HIV stages and maternal and child mortality [ 18 20 ]. Evidence shows that younger age, lack of education, stigma and discrimination, failure to disclose HIV-status, long distances to reach health facilities, long waiting times, poor adherence to treatment, high CD4 count and WHO clinical stage I, II were associated with LTFU [ 21 – 23 ].…”
Section: Introductionmentioning
confidence: 99%